SYED MUHAMMAD NAQUIB AL ATTAS'S PHILOSOPHY OF EDUCATION: A PERENNIALIST CRITICISM OF THE SECULARIZATION OF EDUCATION - Anugrah Giffari; Hironimus Dafa; Ishomuddin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This article investigates the perennialist philosophical critique by Syed Muhammad Naquib Al-Attas of the secularization of education, which is identified as the source of the modern educational crisis, a crisis marked by pragmatism and the erosion of values. This research analyzes Al-Attas's body of work to unveil his critique. The findings show that Al-Attas perceives secularization not just as a political process, but rather as a philosophical program that leads to the desacralization of nature and the despiritualization of man. The most damaging consequence in education is the